Effectiveness of a Technology-Enhanced Integrated Care Model for Frail Older People: A Stepped-Wedge Cluster Randomized Trial in Nursing Homes. (15th July 2020) - Kim, Hongsoo; Jung, Young-il; Kim, Gi-Soo; Choi, Hyoungshim; Park, Yeon-Hwan
Abstract: Background and Objectives: The objective of this study was to evaluate the impact of an information and communication technologies (ICT)-enhanced, multidisciplinary integrated care model, called Systems for Person-centered Elder Care (SPEC), on frail older adults at nursing homes. Research Design and Methods: SPEC was implemented at 10 nursing homes in South Korea in random order using a stepped-wedge design. Data were collected on all participating older residents in the homes before the first implementation and until 6 months after the last implementation. The 21-month SPEC intervention guided by the chronic care model (CCM) consists of 5 strategies: comprehensive geriatric assessment, care planning, optional interdisciplinary case conferences, care coordination, and a cloud-based ICT tool along with a free messaging app. The primary outcome was quality of care measured by a composite quality indicator (QI) from the interRAI assessment system. Usual care continued over the control periods. Nursing home staff were not blinded to the intervention. Results: There were a total of 482 older nursing home residents included in the analysis. Overall quality of care measured by the composite QI was significantly improved (adjusted mean difference: −0.025 [95% CI: −0.037 to −0.014, p < .0001]). The intervention effect was consistent in the subgroup analysis by cognition and activities of daily living. There were no important adverse events or side effects. Discussion and Implications: The SPEC, a CCM-guided, ICT-supported, multidisciplinary integrated care management intervention, can improve the quality of care measured by health and functional outcomes for frail older persons residing in nursing homes with limited health care provision. Clinical Trials Registration Number: ISRCTN11972147